Russian Cultural Conservatism Critiqued: Translating the Tropes of 'Gayropa' and 'Juvenile Justice' in Everyday Life. Issue 8 (14th September 2021) - Morris, Jeremy; Garibyan, Masha
Abstract: Framing the 'conservative turn' in Russia as a 'culture war' casts ordinary Russians as an amorphous reactionary mass, willingly following political entrepreneurs' cues of intolerance. This essay rejects that interpretation and seeks to restore agency to ordinary Russians. Based on ethnographic encounters discussing homophobia and heteronormative gender and family attitudes, the essay argues that vernacular social conservatism re-appropriates official discourses to express Russians' feelings towards their own state. Intolerance is less fuelled by elite cues but rather reflects domestic resentment towards, and fear of, the punitive power of the state, along with nostalgia for an idealised version of moral socialisation under socialism.